Implikasi Teologi Kaum Puritan bagi Kehidupan Gereja di Indonesia - Lado, Gatsper Anderius (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2024)
The lack of correct understanding and weak teachings of the church regarding holiness are actual problems throughout time. Political influences and a world that has been damaged by sin have become a challenge for believers to live a holy life. The church needs to be purified constantly. The church's weak understanding and teaching about biblical holiness will have an impact on the weak quality of Christian faith. The Puritans who emerged in the 16th century AD in England were famous for their teachings which prioritized the application of biblical teachings, holy living behavior and missionary duties. The theology of the Puritans was then believed by theologians to be the forerunner for the development of the Evangelical (Evangelical) Movement today. For this reason, Puritan theology is worthy of study and becomes a guide for improving the quality of church life today, including in Indonesia. Using literature study research methods, this article highlights the emphasis and characteristics of Puritan theology only, and does not discuss the entire Puritan theological building as a topic of discussion. This paper aims to examine matters related to Puritan theology or teachings using a literature study approach. The research results show that Puritan theology emphasizes the importance of churches in Indonesia to teach and practice Puritan theology as a benchmark for remaining firm in upholding the teachings of the Bible as a basis for conducting theology and living holy lives in a holistic manner and faithfully preaching the Gospel of Christ.AbstrakKurangnya pemahaman yang benar dan lemahnya pengajaran gereja perihal kekudusan menjadi permasalahan aktual di sepanjang masa. Pengaruh politik dan dunia yang sudah dirusak oleh dosa, menjadi tantangan bagi orang percaya untuk menjalankan perilaku hidup kudus. Gereja perlu dimurnikan senantiasa. Lemahnya pemahaman dan pengajaran gereja tentang kekudusan yang alkitabiah, akan berdampak pada lemahnya kualitas iman Kristen. Kaum Puritan yang muncul Abad ke-16 Masehi di Inggris terkenal dengan pengajaran yang mengutamakan penerapan ajaran alkitab, perilaku hidup kudus dan tugas misi.Teologi Kaum Puritan kemudian diyakini para teolog menjadi cikal bakal bagi berkembanganya Gerakan Injili (Evangelikal) pada masa kini.  Untuk itu, teologi Kaum Puritan layak dipelajari dan  menjadi panduan bagi peningkatan kualitas kehidupan gereja masa kini, tak terkecuali di Indonesia. Dengan menggunakan metode penelitian Studi Pustaka, artikel ini menyorot penekanan dan ciri khas teologi Kaum Puritan saja, dan tidak membahas keseluruhan bangunan teologi Kaum Puritan sebagai topik diskusi. Paper ini bertujuan untuk mengkaji hal-hal yang berhubungan dengan teologi atau ajaran kaum Puritan dengan memakai pendekatan Studi Pustaka. Hasil penelitian menunjukkan bahwa  teologi Kaum Puritan menekankan pentingnya gereja-gereja di Indonesia untuk mengajarkan dan mempraktekkan teologi Kaum Puritan menjadi patokan untuk tetap teguh memegang ajaran Alkitab sebagai landasan dalam berteologi dan berperilaku hidup kudus secara holistik serta setia memberitakan Injil Kristus.